Utilisation of Natural Resources as a Source of Inspiration and Innovation in SME Development - Abu Muna Almaududi Ausat; Ramaswamy Velmurugan; Mohammed Mudher Mazil; Muhammad Ahmad Mazher; Moses Odhiambo Okombo (CV. Media Digital Publikasi Indonesia, 2023)
Natural resources are an invaluable asset for every country. Utilisation of natural resources can also provide inspiration and innovation in the development of SMEs which is currently one of the important sectors in the Indonesian economy. This research will review the literature related to the potential of natural resources that can be utilised in the development of SMEs as well as strategies that can be used to develop SMEs by utilising natural resources. The research in question is primarily qualitative in nature. The techniques employed to acquire information involve attentive observation and meticulous note-taking, followed by analytical procedures such as data reduction, visualisation, and inference. The results showed that the potential in natural resource utilisation is huge and can provide significant benefits to the local and national economy. SMEs that utilise natural resources effectively and sustainably can increase the added value of products, improve product competitiveness in the global market, and create new jobs. The government, industry players, and the community collaborate in order to make use of natural resources as a source of inspiration and innovation in the process of developing SMEs